Chemicals aáociated with maize resistance to corn earworm and fall armyworm - Snook, M.E.=700 1 Wiseman, B.R.; Widstrom, N.W.; Wilson, R.L.
Sumario (En)
Ilus.; 11 ref.
Keywords: ZEA MAYS; RESISTENCIA A LAS PLAGAS; HELICOVERPA; SPODOPTERA FRUGIPERDA; TECNICAS ANALITICAS; GERMOPLASMA